2014
DOI: 10.1016/j.pbb.2014.09.021
|View full text |Cite
|
Sign up to set email alerts
|

3,4-Methylenedioxypyrovalerone (MDPV)-induced conditioned taste avoidance in the F344/N and LEW rat strains

Abstract: The inbred Fischer (F344) and Lewis (LEW) rats, while originally developed as animal models for cancer and tissue transplantation research, have since been used to study genetic differences in a variety of physiological and behavioral endpoints. In this context, LEW rats show greater sensitivity to the aversive effects of cocaine as compared to F344 rats in a conditioned taste avoidance procedure. Like cocaine, 3,4-methylenedioxypyrovalerone (MDPV; “Bath Salts”) acts as a dopamine transport blocker and possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
3
18
1
Order By: Relevance
“…The temperature change in the hypo thermic direction was what would be predicted for rats evaluated under the 21°C ambient temperature condition of this study based on prior findings for MDMA (Malberg and Seiden 1998), methamphetamine (Gilpin et al 2011; Miller et al 2013f; Myles et al 2008) and mephedrone (Aarde et al 2013a; Miller et al 2013a; Wright et al 2012) as well as the non-substrate, transporter inhibitor cocaine (Cox and Lee 1979) and dopamine direct agonist apomophine (Brown et al 2007). Differences with prior reports of hyperthermic effects of MDPV in rats are likely due to ambient temperature, strain and especially light cycle differences (King et al 2014; Kiyatkin et al 2015). …”
Section: Discussioncontrasting
confidence: 76%
“…The temperature change in the hypo thermic direction was what would be predicted for rats evaluated under the 21°C ambient temperature condition of this study based on prior findings for MDMA (Malberg and Seiden 1998), methamphetamine (Gilpin et al 2011; Miller et al 2013f; Myles et al 2008) and mephedrone (Aarde et al 2013a; Miller et al 2013a; Wright et al 2012) as well as the non-substrate, transporter inhibitor cocaine (Cox and Lee 1979) and dopamine direct agonist apomophine (Brown et al 2007). Differences with prior reports of hyperthermic effects of MDPV in rats are likely due to ambient temperature, strain and especially light cycle differences (King et al 2014; Kiyatkin et al 2015). …”
Section: Discussioncontrasting
confidence: 76%
“…It is interesting that no significant changes in body temperature at any dose of MDPV were observed. Psychostimulants typically increase body temperature immediately following administration (King et al, 2014). A recent report also showed that MDPV can increase body temperature (King et al, 2014), but it should be noted that others did not find an effect of MDPV on body temperature (Aarde et al, 2013;Merluzzi et al, 2014) or body temperature changes that are associated with ambient temperature conditions .…”
Section: Discussionmentioning
confidence: 99%
“…That pre-exposure to MDPV also attenuated cocaine-induced taste avoidance is interesting in light of the fact that the neurochemical mechanism(s) mediating cocaine’s actions are not identical to those of MDPV. Specifically, although both MDPV and cocaine inhibit the reuptake of the monoamines at their respective transporters, i.e., DAT, NET and SERT, MDPV is more potent than cocaine at inhibiting the reuptake of dopamine (MDPV: IC 50 4.1 ± 0.6 nM, COC: IC 50 211 ± 19 nM) and norepinephrine (MDPV: IC 50 25.9 ± 5.6 nM, COC: IC 50 292 ± 34 nM), and less potent at inhibiting the reuptake of serotonin (MDPV: IC 50 3305 ± 485 nM, COC: IC 50 313 ± 17 nM) with DAT/SERT ratios of 806:1 (MDPV) compared to 1.5:1 (cocaine) (Glennon and Young, 2016; Karch 2015; King et al, 2014b; Marusich et al, 2014; Simmler et al, 2013). Given their shared (but not identical) mechanisms of action, it is not surprising that the effects of MDPV pre-exposure on MDPV avoidance were greater than that on cocaine (for a discussion of cross-drug pre-exposure, see Serafine and Riley, 2013).…”
Section: Discussionmentioning
confidence: 99%